Metabolic Engineering and Comparative Performance Studies of Synechocystis sp. PCC 6803 Strains for Effective Utilization of Xylose - Ranade, Saurabh; Zhang, Yan; Kaplan, Mecit; Majeed, Waqar; He, Qingfang (Frontiers in Microbiology, 2015)
Wood sugars such as xylose can be used as an inexpensive carbon source for biotechnological applications. The model cyanobacterium Synechocystis sp. PCC 6803 lacks the ability to catabolize wood sugars as an energy source. Here, we generated four Synechocystis strains that heterologously expressed XylAB enzymes, which mediate xylose catabolism, either in combination with or without one of three xylose transporters, namely XylE, GalP, or Glf. Except for glf, which is derived from the bacterium Zymomonas mobilis ZM4, the heterologous genes were sourced from Escherichia coli K-12. All of the recombinant strains were able to utilize xylose in the absence of catabolite repression. When xylose was the lone source of organic carbon, strains possessing the XylE and Glf transporters were most efficient in terms of dry biomass production and xylose consumption and the strain lacking a heterologous transporter was the least efficient. However, in the presence of a xylose-glucose mixed sugar source, the strains exhibited similar levels of growth and xylose consumption. This study demonstrates that various bacterial xylose transporters can boost xylose catabolism in transgenic Synechocystis strains, and paves the way for the sustainable production of bio-compounds and green fuels from lignocellulosic biomass.